Taming big data with Apache Spark and Python--Hands on! - Kane, Frank; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2016)
"Apache Spark has emerged as the next big thing in the Big Data domain -- quickly rising from an ascending technology to an established superstar in just a matter of years. Spark allows you to quickly extract actionable insights from large amounts of data, on a real-time basis. This course will be your companion to learn Apache Spark in a hands-on manner. Start with understanding how to set up Spark on a single system or on a cluster. From analyzing large data sets using Spark RDD, to developing and running effective Spark jobs quickly using Python, this course will teach you everything. Packed with over 15 interactive, fun-filled examples relevant to the real-world, the course will empower you to understand the Spark ecosystem and implement production-grade real-time Spark projects with ease."--Resource description page.
Title from resource description page (Safari, viewed January 10, 2017).
Presenter, Frank Kane.
Keywords: Data mining; SPARK (Electronic resource); Python (Computer program language); Big data; Electronic books